2014
DOI: 10.21829/myb.2014.203155
|View full text |Cite
|
Sign up to set email alerts
|

Desarrollo de pellets a partir de tres especies leñosas bajo condiciones mediterráneas

Abstract: La biomasa leñosa como recurso energético varía según tres factores: 1) especie, 2) condiciones ambientales que influyen en su producción y 3) dispersión en el territorio. La estimación de la aptitud de este recurso es crucial para el desarrollo sustentable del sector agroforestal y, en concreto, de la cadena de valor bosque-industria-consumo. Tomando en cuenta esta situación, el objetivo de este documento consistió en determinar la aptitud de tres tipos arbóreos como biocombustible sólido. Una especie foresta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
1
4
0
4
Order By: Relevance
“…Therefore, this species can be used as a raw material for transformation into densified biofuel for domestic or industrial applications. These results are in accordance with those reported by different authors [40,44,97,103,104]. Herrera-Fernández et al [94] found values below those found here of 17 MJ/kg for three species of oak.…”
Section: Calorific Valuesupporting
confidence: 94%
See 2 more Smart Citations
“…Therefore, this species can be used as a raw material for transformation into densified biofuel for domestic or industrial applications. These results are in accordance with those reported by different authors [40,44,97,103,104]. Herrera-Fernández et al [94] found values below those found here of 17 MJ/kg for three species of oak.…”
Section: Calorific Valuesupporting
confidence: 94%
“…Some studies presented differences in ash content between barked and debarked wood: Barmpoutis et al [95] reported values of 1.62% and 1.14% for wood and 12.18% and 9.15% for Q. coccifera and Q. ilex barks, respectively. Also, Fernández et al [44] found for Q. ilex wood a value of 1.8%. Serret-Guasch et al [96] mentioned an ash content of 0.5% to 2.0% for sawdust from the forestry industry.…”
Section: Immediate Analysismentioning
confidence: 91%
See 1 more Smart Citation
“…A diferencia de otros países pertenecientes a la región europea, en Chile no ha habido experiencia en la producción de biomasa para fines de uso energético con ambas especies mencionadas, y a su vez, existe escasa evidencia científica hasta el momento que permita sustentar el futuro establecimiento masivo de plantaciones productivas dirigidas a fines energéticos (Fernández-Puratich et al, 2014;Muñoz, Cancino, Rodríguez y Olave, 2018). Por lo tanto, la presente investigación consistió en evaluar las características físicas, químicas y energéticas de clones de Miscanthus x giganteus y Paulownia eloganta x fortunei establecidos en tres suelos contrastantes del centro sur de Chile a través de los siguientes objetivos.…”
Section: Introductionunclassified
“…plantations are being cultivated in different countries to produce biomass for the generation of energy (Fernández-Puratich et al, 2014;Senelwa and Sims, 1999). They are also being grown to produce energy crops (Fernández-Puratich et al, 2014;Krasuska et al, 2010;Zegada-Lizarazu et al, 2010), due to the rapid growth. One of the main technical problems for energy production through biomass is the generation of waste, such as fly ash (Ortiz de Zárate et al, 2005).…”
Section: Introductionmentioning
confidence: 99%